EFFECT OF INTERNAL SERVICE QUALITY ON EMPLOYEE SATISFACTION AND ITS IMPACT ON INTERNAL CUSTOMER SATISFACTION DIVISION PORT BONTANG COAL TERMINAL PT INDOMINCO MANDIRI - Syahidul Syahidul; Gusti Noorlitaria Achmad; Syarifah Hudayah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Internal quality service is the important aspect at the organization that can be increase employee satisfaction and internal customer satisfaction. Aim to this research an investigate influence of internal service quality on employee satisfaction with impact to the internal customer satisfaction. This study is focused on the services division especially in port division Bontang Coal Terminal PT. Indominco Mandiri. Researchers took research data through a Google Form questionnaire. A field-survey using a structured questionnaire to PT Indominco Mandiri employees who have a close cooperative relationship with the BoCT port division, such as the STSC division which includes the SC and CBIC divisions, the CHP division and the BoCT port division itself and 84 respondents were recorded as filling in the questionnaire to test all the hypotheses. There are 3 (three) variables in this study namely internal service quality, employee satisfaction and internal customer satisfaction. The data analysis technique used PASW Statistics 18 to test the level of validity and reliability of all items, while to test the results of the hypothesis, the researcher used SEM PLS to determine the relationship between variables. The findings of this study are that the internal service quality variable has a significant positive effect on employee satisfaction, the internal service quality variable has a positive but insignificant effect on internal customer satisfaction, and the employee satisfaction variable has a significant positive effect on internal customer satisfaction. Keywords: Internal Service Quality, Employee Satisfaction, Internal Customer Satisfaction